Psychological detachment and psychological well-being : explicating the role of recovery self-efficacy, neuroticism and affective rumination - Scrooby, Rachel (Stellenbosch : Stellenbosch University, 2024)
Thesis (MCom)--Stellenbosch University, 2024.